Public Participation Practices in Political Life in the Russian Regions - Shapovalova, Inna S.; Zakharov, Victor M.; Hashaeva, Svetlana V.; Pitka, Svetlana V.; Kisislenko, Anastasiya V. (Journal of History Culture and Art Research, 2017)
The article discusses the problem of public participation of the population in the political life of the country. The object of research becomes one of the forms of public participation: people examination. People examination is understood by the authors as an expert opinion initiated by the public, carried out by professionals, conducted in the interests of the people as a whole or of certain social groups, and resulting in the submission of a reasoned conclusion with recommendations for decision-makers. The study of the specifics of the people examination use as an effective public practice was carried out on the basis of the evaluation of the success of the "People examination" project using mass and expert surveys to determine the potential for participation of the population and professional experts in such projects. The research conducted has shown that at present the opinion of citizens living in a specific territory is not always taken into account fully when solving problems of social and economic development. Despite the interest of residents of Russian regions in such projects, the problems of providing general access, information and obtaining a specific result from people examination, do not provide an opportunity to evaluate it as highly effective.